Urgent Transcatheter Arterial Embolization for Wunderlich Syndrome With Hypovolemic Shock Secondary to Ruptured Renal Angiomyolipoma - Gong, Maofeng; Liu, Zhengli; Su, Haobo; Zhao, Boxiang; Kong, Jie; He, Xu (Frontiers in Surgery, 2021)
Purpose Wunderlich syndrome (WS) with hypovolemic shock secondary to ruptured renal angiomyolipoma (rAML) represents an urgent condition. Hence, we reported our experience with transcatheter arterial embolization (TAE) using different embolic materials under this condition. Methods This retrospective study consisted of 22 patients. Embolic materials including particles, microcoils and liquid embolic agents, were selectively used based on the decisions of interventional radiologists. Technical success was defined as the complete occlusion of bleeding vessels on the final renal angiogram. Clinical success was defined as the absence of re-hemorrhage needed for repeat endovascular or surgery treatment after TAE. Results The articulate materials were used when WS presented without aneurysms, a combination of particulate materials and microcoils or Glubran 2 alone were used for WS with aneurysms. The technical success based on 24 episodes of TAEs in 22 patients was 100% (24 of 24). Repeat TAE was achieved in 2 patients with hemorrhage re-occurred two days after the initial embolization with microcoils alone. The clinical success was 90.9% (20 of 22). No nontarget embolization or embolization related complications occurred during the TAE procedure. 27.3% of patients (6 of 22) experienced minor complication of post embolization syndrome. During a median follow-up time of 34.0 months (range, 3-95 months), no recurrent hemorrhage that required repeat endovascular or surgical treatment for hemostasis occurred. Conclusion Urgent TAE with the selective use of different embolic materials is an effective alternative to control WS with hypovolemic shock secondary to ruptured rAML. The condition whether with aneurysms may determine the embolic materials employed.